PENGARUH GAYA KEPEMIMPINAN, REWARDDAN PUNISHMENT TERHADAP MOTIVASI KERJA PADA PT. KARYANUSA EKA DAYA DI KABUPATEN KUTAI TIMUR - masni, masni (OBOR: Oikonomia Borneo, 2021)
Masni: The Effect of Leadership Style, Reward and Punishment on Work Motivation at PT. Karyanusa Eka Daya, East Kutai Regency. (under the guidance of Advisory Lecturer I Mr. Suyanto and Supervisor II Mrs. Meinard Maya Safitri) The importance of employees who cover the role of utilization and management of employees is needed to grow the work ethic of employees, the company must comply with a number of requirements by applying effective HR management techniques and concepts, namely from how someone leads, rewards and punishments. The effectiveness of achieving the company's vision is strongly influenced by the role of the leader. A leader must be able to influence and direct appropriately so that employees are willing to carry out their work without coercion and are happy to work together to realize company goals. The research objective to be achieved is to find out and analyze whether the Leadership Style, Reward and Punishment have a partial or simultaneous effect on Work Motivation on Employees of PT. Karyanusa EkaDaya, East Kutai Regency. Based on the research, the results obtained partially that the leadership style variable has no significant positive effect on work motivation at PT. Karyanusa Eka Daya, East Kutai Regency. Partially, the reward variable has a significant positive effect on work motivation at PT. Karyanusa Eka Daya, East Kutai Regency. Partially, the punishment variable has no significant negative effect on work motivation at PT. Karyanusa Eka Daya, East Kutai Regency. Simultaneously the variables of leadership style, reward, punishment have a significant positive effect on work motivation at PT. Karyanusa Eka Daya, East Kutai Regency. Keywords: Leadership Style, Reward, Punishment and Work Motivation